Parametric Optimization of Electric Discharge Machining for AISI 1045 Steel - Muhammad Mansoor Uz Zaman Siddiqui; Syed Amir Iqbal; Ali Zulqarnain; Adeel Tabassum (Memoria Investigaciones en Ingeniería)
This study investigates the optimization of Electric Discharge Machining (EDM) parameters for AISI 1045. It is a medium carbon steel which is commonly used in automotive and aerospace industries because of its balanced strength, toughness and machinability. However, achieving optimal machining efficiency with excellent surface finish in short time and without wasting excess material with EDM remains a challenge at large. The research focuses on optimizing key EDM input parameters like current (LV), voltage (HV), pulse on time (Ton) and pulse off time (Toff), to improve machining time (Tm), material removal rate (MRR), electrode wear rate (EWR), surface roughness (Ra) and base radius (R). Full factorial design and Response Surface Methodology (RSM) were used to conduct experiments, and ANOVA was employed to identify the most significant factors influencing the output responses. Multi-objective optimization was performed through the desirability function and the findings were validated by repeated experiments. The results showed that pulse on time (Ton), its interaction with pulse off time (Toff) and the three-factor interaction between current (LV), Ton and Toff were the most significant factors affecting machining performance. Optimizing these parameters reduced machining time (Tm) to 623.21 seconds thus significantly improving EDM efficiency. The material removal rate (MRR) was maximized at 0.0173 g/min resulting in considerable increase in material removal efficiency. The electrode wear rate (EWR) was minimized to 0.0088 g/min, which prolongs electrode life and reduces operational costs. Surface roughness (Ra) was improved to 0.0253 mm, ensuring a high-quality surface finish. The base radius (R) was successfully optimized to 1.5298 mm, aligning closely with the desired target of 1.5 mm thus ensuring dimensional accuracy. This investigative study of optimization of parameters for EDM of AISI 1045 material is extremely significant for automotive and aerospace industries that rely on precision machining, as the optimized EDM parameters lead to improved efficiency, reduced material waste and enhanced product quality. These findings offer valuable insights for improving EDM processes, particularly in sectors requiring complex geometries and high precision, such as automotive and aerospace manufacturing.